Assessment of the Immune Effect and Safety of Cell Culture-Derived Influenza Vaccine from Egg-Derived by Meta Analysis - Geng, Xingliang; Liu, Ze; Liao, Guoyang (International Journal of Innovative Research in Medical Science, 2020)
Objective: The study was to evaluate the immune effect and safety difference of cell culture-derived influenza vaccine from egg-derived by meta analysis; Methods: It selected the article about clinical trials through medline, embase, cochrane library, FEBM, clinicaltrials.gov, WHO, and International Standard Randomised Controlled Trial Number Registry. There was no language restrictions (update to Apr 25, 2016). The threshold should contain cell culture-derived or egg-derived influenza vaccine for human beings; Result: It showed enough immune effect and accepted safety by using cell culture-derived influenza vaccine, compared with egg-derived influenza vaccine; Conclusion: The cell culture-derived influenza vaccine could be used for human after clinical trials, not differ from egg-derived.